2016
DOI: 10.1051/shsconf/20162902043
|View full text |Cite
|
Sign up to set email alerts
|

The nature of the relationships between personality and cognitive characteristics

Abstract: Abstract. In the current study we investigated the contribution of genetic and environmental factors to the relationship between the Big Five personality traits and nonverbal intelligence assessed with Raven's Standard Progressive Matrices. The sample included a total of 290 people: 59 monozygotic (MZ) and 86 dizygotic (DZ, 58 same-sex and 28 opposite-sex) twin pairs aged 14 to 20 years (mean age = 15.84, SD = 1.05). The phenotypic correlations between the traits and intelligence scores were non-significant, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
(14 reference statements)
3
3
0
Order By: Relevance
“…As we expected, the accuracy of the RAPM task was generally correlated to one's openness, at least measuring by the O scale of CBF-PI-B. The result was consistent with those of previous studies (DeYoung et al, 2005 ; Voronin et al, 2016 ). The only point unlike the previous studies using NEO-PI scale, openness was more modestly associated with RAPM (the Pearson's r between openness scale and RAPM was round 0.3, p < 0.01) in this work.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As we expected, the accuracy of the RAPM task was generally correlated to one's openness, at least measuring by the O scale of CBF-PI-B. The result was consistent with those of previous studies (DeYoung et al, 2005 ; Voronin et al, 2016 ). The only point unlike the previous studies using NEO-PI scale, openness was more modestly associated with RAPM (the Pearson's r between openness scale and RAPM was round 0.3, p < 0.01) in this work.…”
Section: Discussionsupporting
confidence: 92%
“…Even so, the significant difference between the accuracy of the two tasks in high and medium openness groups indicated that their being sensitive to cognitive ability (fluid vs. crystallized) was different. Regarding the RTs in each task, in agreement with previous studies, openness did not correlate with the overall computational speed (Bates and Shieles, 2003 ; Voronin et al, 2016 ). This indicated that levels of openness might not substantially influence an individual's attention and concentration during relatively long-time reasoning.…”
Section: Discussionsupporting
confidence: 91%
“…Most of these batteries have been developed for the clinical use (NAB, CNTB, [19,20]). However, they have also been successfully used to study the normative sample [15,21,22]. We have also showed its advantages in the behavioral genetics studies [23].…”
Section: Analysis Of Platforms For Psychological Researchmentioning
confidence: 92%
“…Widely used cognitive characteristics include general cognitive abilities, working memory [9], spatial or mathematical abilities [10] Most of these batteries have been developed for clinical use NAB [11]. However, they have also been used successfully to study regulatory samples [12] , as well as for research in the field of behavioral genetics [13].…”
Section: Introductionmentioning
confidence: 99%